Evolution of cutaneous tuberculosis over the past 30 years in a tertiary hospital on the European Mediterranean coast. (22nd October 2012) - Marcoval, J.; Alcaide, F.
Summary Background. There have been few studies on cutaneous tuberculosis (TB) in Europe in recent years. Objective. To retrospectively analyse the evolution of the various types of cutaneous TB over the past 30 years in an adult population in Spain. Methods. Patients with cutaneous TB diagnosed between 1981 and 2011 at Bellvitge Hospital, Barcelona, Spain, were included in the study. Chest radiography was performed for all patients, and the presence of TB elsewhere in the body was excluded when clinically suspected. Results. In total, 36 patients (15 male, 21 female, mean age 53.72 years) were diagnosed with cutaneous TB. There were 22 patients with lupus vulgaris (LV), 4 with scrofuloderma, 4 with miliary TB, 3 with tuberculous abscess/ulcer, and 1 each with orificial TB, warty TB, and an iatrogenic inoculation from underlying visceral focus. Of the 36 patients, 16 (38.88%) had TB presenting simultaneously in other organs. Mycobacterial culture from skin biopsies was positive for Mycobacterium tuberculosis complex in 17 of the 32 cases tested (53.12%), whereas stains for acid‐fast bacilli in skin samples were positive in only 3 of 36 patients (8.33%). Conclusions. Although the number of cases of cutaneous TB diagnosed yearly in our population has declined over the past 30 years, cutaneous TB still exists in Europe, and its incidence is expected to increase, owing to the increased immigration into the continent in recent years. The most common type of cutaneous TB in our adult population was LV. It should be noted that despite being considered a benign form of TB, cutaneous TB can be accompanied by TB in internal organs, and severe complications can occur, such as the development of squamous cell carcinoma in long‐lasting lesions.